Development of Integrated GreenVec Biofeedback Game with Galvanic Skin Response Sensor - Muhammad Nubli, Abdul Wahab; Noraziah, Ahmad; Muhd Azrulnizam, Suna Abdullaha; Herawan, Tutut; Ho, Cheong Lee (2013)
GreenVec Biofeedback Game (GVBG) is a biofeedback game-based application that able to measure the skin conductivity of the player with the integration of Galvanic Skin Response (GSR) sensor. The measurement of the skin conductivity is crucial as an indicator for human meditation improvement in terms of stress control. In addition, GVBG spread awareness on global green technology issues specifically about the Electric Vehicles (EV) issue to all users throughout the game process. The measured Skin Conductivity Level (SCL) corresponds to the player’s awareness level about the green EV. During the development, Spiral Methodology is applied for a smoother and clearer development processes. GVBG is mainly developed by using Microsoft Visual Studio 2008 with XNA Framework 3.1 and Adobe Photoshop CS6. By playing GVBG, the user will be able to learn more about the proper way to reduce stress while gain awareness on the green technology issues related with Electric Vehicles.